Workshop Penggunaan Media Manipulatif Matematika Materi Pecahan Bagi Guru Sekolah Dasar Bengkulu Selatan - Agus Susanta; Irwan Koto (DHARMA RAFLESIA, 2022)
Learning mathematics, especially in elementary schools, needs an emphasis on concrete operations. So a tangible form is needed in representing a mathematical concept. Problems in schools are the lack of availability of manipulative media, lack of understanding and skills of teachers about manipulative media for learning mathematics. Even though the design and manufacture of manipulatives is easy for teachers to do. Making manipulative mathematical media is one of the teacher's activities to support teaching tasks, especially in preparing learning tools such as student worksheets. The purpose of this service is to improve the ability of teachers at SD Negeri 78 Bengkulu Selatan. The activity was held at SD Negeri 78 Bengkulu Selatan with the target of serving as many as 20 teachers. The implementation of the preparation consists of four stages, namely: (1) module design, (2) training in the use of teaching aids, (3) structured assignments. The results of service activities are an increase in teachers' ability and responses to training activities.